2001
DOI: 10.1037/h0089469
|View full text |Cite
|
Sign up to set email alerts
|

The health system and emotional care: Validating the many meanings of spontaneous pregnancy loss.

Abstract: Healthcare professionals can powerfully influence how women experience pregnancy loss. However, such professionals often work with professional and cultural assumptions of how women should respond to pregnancy loss and fail to provide their patients with sensitive and appropriate emotional care. In this study, the authors used Charmaz' constructionist grounded theory, a qualitative approach, to generate and analyze interviews of eight participants with different familial and socioeconomic backgrounds. It was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
(62 reference statements)
1
43
0
Order By: Relevance
“…Women emphasise the lack of emotional support and sensitivity (Cuisinier, Kuijpers, Hoogduin, de Graauw & Janssen, 1993;Lasker & Toedter, 1994;Paton, Wood, Bor & Nitsun, 1999), their need for structured intervention, and specific information regarding the implications of their miscarriage (Cecil, 1994;Wong, Crawford, Gask & Grinyer, 2003). Corbet-Owen and Kruger (2001) underline in particular the need that women have for having their thoughts and feelings validated by health care professionals. According to a study in France, 43% of women would want their psychological distress recognised and validated and 32% feel the need for psychological support (Garel et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Women emphasise the lack of emotional support and sensitivity (Cuisinier, Kuijpers, Hoogduin, de Graauw & Janssen, 1993;Lasker & Toedter, 1994;Paton, Wood, Bor & Nitsun, 1999), their need for structured intervention, and specific information regarding the implications of their miscarriage (Cecil, 1994;Wong, Crawford, Gask & Grinyer, 2003). Corbet-Owen and Kruger (2001) underline in particular the need that women have for having their thoughts and feelings validated by health care professionals. According to a study in France, 43% of women would want their psychological distress recognised and validated and 32% feel the need for psychological support (Garel et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The current study of the psychological experiences of nurses in a maternity ward of a Western Cape state hospital formed part of a larger longitudinal study concerned with the emotional experiences of poor rural women during pregnancy, birth and the postpartum period (BurmeisterNel, 2005;Corbet-Owen & Kruger, 2002;Grossman, Kruger & Moore, 1999, 2000Kruger, 2003;Kruger & Van der Spuy, 2005;Lazarus & Kruger, 2004, 2004aSmit, 2002;Spies, 2001). Preliminary findings of the larger study strongly indicated that poor women who were participants in this study often experienced the nurse-patient relationship in the maternity ward as highly compromised -an experience that certainly impacted on their health-seeking practices (Kruger & Van der Spuy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The trauma experienced from a single miscarriage has been described as a "shock" trauma while the trauma in recurrent miscarriage has been described as a "strain" trauma because grieving often extends for a longer period of time with the anticipation of further loss (Katz and Kuller, 1994). While some individuals/couples have minimal emotional upset, others experience negative psychological reactions for months, and others develop chronic psychiatric morbidity (Corbet-Owen and Kruger, 2001;Craig et al, 2002;Madden, 1994). The intensity of these emotional reactions is not uniformly correlated with gestational age at the time of loss, presence or number of living children, maternal age or number of previous miscarriages (Craig et al, 2002;Klock et al, 1997;Swanson, 2000).…”
Section: Vignettementioning
confidence: 99%